Optimal Allocation of Land between Productive Use and Recreational Use. - Giménez, Eduardo L.; González-Gómez, Manuel (Journal of Regional Science, 2003)
This paper is an inquiry into the optimal allocation of time and natural areas to recreational uses, which have the feature of being a pure and continuous public good. We address this issue with a comprehensive approach. A static rational general equilibrium framework is developed in which heterogeneous agents allocate land and time endowments between alternative uses. This modeling has important advantages. First, Pareto-optimal and voluntary-contribution equilibrium allocations are obtained in a unified set-up. Second, the suboptimality result of the decentralized equilibrium, the free-rider problem on the provision of this nonexcludable public good, and different mechanisms to return the economy to its first-best are analyzed. Finally, a methodological critique is made of some empirical literature, and it is suggested that our theoretical microeconomic-based structure seems to be a suitable starting point for empirical research. Reprinted by permission of the publisher.